Economic Sanctions, 1960-2022: Targets, Structure, Impact - Marina V. Niyazova (Vestnik RUDN. International Relations)
Economic globalization not only leads to significant changes in the international economic system, but also to the formation of the institution of economic sanctions. It identifies the targets, structure and consequences of economic pressure on sovereign states in the context of economic globalization. Methodologically, the study is based on the dialectical method, which implies the study of phenomena in constant development and interrelation, in addition to methods of comparative and structural analysis, abstraction, synthesis and others. A special feature of the study is the inclusion of data from the Global Sanctions Data Base together with the World Bank and the United Nations Conference on Trade and Development (UNCTAD) on the socio-economic indicators of the objects and subjects of sanctions since 1960. The author concludes that the intensification of sanctions over the past three decades has more to do with the declining share of major actors in international production and trade than with concerns about, for example, territorial integrity and human rights. A study of the sanctions’ dynamics and their impact on the socio-economic development of the most popular objects (Afghanistan, Iran, Libya, Myanmar and Russia) reveals a cyclical nature of the processes. After the peak of sanctions pressure, the intensity of sanctions pressure diminishes, although unilateral economic measures are lifted more slowly, especially financial ones, the value of which gradually increases. It is evident that trade sanctions are more frequently lifted, while visa restrictions are less frequently imposed. This reveals the impact of economic sanctions on the sanctioned country in general is often overstated or considered to be short-term. The size of the sanctioned country’s economy remains a significant barrier to negative effects. However, the effects of economic sanctions on the (economically active) population are more noticeable and may lead to an increase in the gap of their national income and well-being with the global level. The impact of sanctions on the global economic landscape is evident, with their intention being to preserve the prevailing distribution of wealth and power, favoring the declining economies of the United States and the United Kingdom while concurrently fortifying those of China, India, and other emerging economic powers. The following conclusions and recommendations are posited for the purpose of enhancing the adjustment policy of the sanctioned country.